REVITALISASI PERADILAN ADAT PADA MASYARAKAT NGADA BERBASIS KEARIFAN LOKAL - Rato, Dominikus (Faculty of Law, Universitas Sebelas Maret, 2015)
AbstractThe aim of this study to develop conflict resolution options or alternatifve dispute resolution in the local-knowlegde perspective in woe community in Ngada. In the socio-cultural reality that local knowledge is plural. Diversity of local knowledge based on the local community cosmology. Conflict resolution is always directed towards harmony. With socio-legal approach was found that adat-land dispute resolution perspective on the local knowledge in Ngadhu- bhaga community oriented perspectives such. Dispute resolution pattern in the local knowledge perspectives begins in the family, if the conflict comes from inside relatives or clan. But, if the conflict is sourced from inter- community/relatives/clan, then the chairman of the indigenous, traditional elders, who called mosalaki consulted. Mosalaki role tailored to the competencies and their respective duties. The division of tasks/roles is done by itself, according to custom and personal awareness and recognized together. It is recommended that in the event of a conflict, especially indigenous lands, the functionaries traditional law, mosalaki given first before being taken to the formal justice institutions. If the decision of the mosalaki has been accepted and implemented, then taken to the legal system, the nebis in idem principles can be applied.AbstrakTujuan penulisan ini adalah untuk mengembangkan alternatif penyelesaian konflik atau sengketa melalui perspektif pengetahuan lokal di komunitas Woe di Ngada. Dalam kenyataan sosiokultural, pengetahuan lokal bersifat plural. Keberagaman pengetahuan lokal didasarkan atas kosmologi. Penyelesaian konflik diarahkan pada harmoni. Pendekatan sosio-legal menemukan bahwa perspektif yang berlaku dalam penyelesaian konflik di Ngadhubhaga merupakan penyelesaian yang berorientasi pada kehidupan komunitas. Pola penyelesaian sengketa bersumber dari keluarga apabila konflik berawal dari dalam kerabat atau klan. Namun apabila konflik merupakan sengketa antar-komunitas/kerabat/klan, maka pemimpin komunitas, tetua adat yang disebut mosalaki, bertindak selaku konsultan. Peran mosalaki bergantung pada kompetensi dan tugas-tugasnya. Pembagian tugas dilakukan oleh dirinya sendiri, bergantung pada kebiasaan, kesadaran pribadi, dan telah diketahui bersama-sama. Dalam sebuah konflik, terutama yang berkaitan dengan tanah adat, direkomendasikan untuk dapat diselesaikan terlebih dahulu oleh mosalaki sebelum menempuh jalur hukum nasional. Apabila keputusan yang diambil mosalaki dapat diterima dan diterapkan, bila selanjutnya diselesaikan melalui sistem hukum nasional, maka prinsip nebis in idem dapat diterapkan.